Domichnial Borings in Serpulid Tube Walls: Prosperous Benthic Assemblages in the Cretaceous of France and the Czech Republic - Mikuláš, Radek; Kočová Veselská, Martina; Kočí, Tomáš; Šamánek, Jaroslav; Jäger, Manfred; Heřmanová, Zuzana; Bruthansová, Jana (Frontiers in Ecology and Evolution, 2022)
The calcareous tubes inhabited by some polychaetes (some Serpulidae and the sabellid Glomerula) which are adapted to live sticking in soft ground, starting from the Permian, represent widespread but widely neglected and understudied substrates for domichnial bioerosion. Serpulids can be considered small macrofauna. However, due to the thinness of serpulid tubes, borings in them are sized in the order of 0.01–0.9 mm in diameter and thus rather considered micropaleontological objects. Extensive and methodologically broad search (vacuum castings studied at SEM; micro-computed tomography) for and study of borings in these specific substrates was performed on material from the Cenomanian of Le Mans area (France) and the Cenomanian and Turonian of the Bohemian Cretaceous Basin (Czechia). It shows that the bioerosive traces can be assigned to the existing ichnogenera Rogerella, Trypanites, Entobia, Maeandropolydora, and Iramena. Somewhat surprising is the frequency and disparity of dwelling borings. Several clues, especially in the more abundant ichnogenera Rogerella, Trypanites, and Entobia, support the hypothesis that the tracemakers of these borings adapted to the small size of their substrates by necessarily staying very small by themselves but nevertheless living to adulthood.